2009
DOI: 10.1097/01.ogx.0000349788.10461.a7
|View full text |Cite
|
Sign up to set email alerts
|

Interpretability of Excisional Biopsies of the Cervix: Cone Biopsy and Loop Excision

Abstract: Limited data are available on the attitudes of gynecologists regarding mode of hysterectomy for benign indications. This cross-sectional study used a postal questionnaire to assess attitudes of members of the Swedish Society of Obstetrics and Gynecology toward mode of benign hysterectomy. The choices of mode of hysterectomy were total abdominal hysterectomy, subtotal abdominal hysterectomy, laparoscopic or laparoscopically-assisted hysterectomy, and vaginal hysterectomy (VH). Participants were asked questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
1
16
0
1
Order By: Relevance
“…The LEEP has been associated with an increased number of specimens, which limits interpretability, and an increased number of positive margins. 12,13 Ideally, conization should yield a single interpretable specimen and disease-free margins. Miroshnichenko et al 13 reported that LEEP was less likely to yield a single intact specimen and that an increase in the number of specimens obtained had a statistically significant negative effect on pathologic interpretability.…”
Section: Discussionmentioning
confidence: 99%
“…The LEEP has been associated with an increased number of specimens, which limits interpretability, and an increased number of positive margins. 12,13 Ideally, conization should yield a single interpretable specimen and disease-free margins. Miroshnichenko et al 13 reported that LEEP was less likely to yield a single intact specimen and that an increase in the number of specimens obtained had a statistically significant negative effect on pathologic interpretability.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple-pass LEEP is not an uncommon practice, but it has been reported as a risk factor for unevaluable margins [6,7]. In the present study, the rate of multiple passes (nearly 40%) was twice the maximum rate recommended (20%) [4].…”
Section: Discussionmentioning
confidence: 73%
“…The panel favored the use of CKC for patients in whom microinvasive cervical cancer was suspected. 51 The LEEP has been associated with a cautery artifact that may compromise the pathologic evaluation of the tissue specimen. Diagnosis of microinvasive or invasive cancer at cervical biopsy requires treatment according to the NCCN Guidelines for Cervical Cancer (in this issue and at www.NCCN.org).…”
Section: Satisfactory Colposcopy For Lsil or Asc-usmentioning
confidence: 99%
“…CKC is performed for microinvasive biopsy findings; CKC or LEEP can serve as definitive treatment if the lesion is confirmed to be intraepithelial. 51 A diagnosis of microinvasive or invasive cancer on cervical biopsy, LEEP, or CKC requires treatment according to the NCCN Guidelines for Cervical Cancer (in this issue and at www.NCCN.org).…”
Section: Unsatisfactory Colposcopy For Lsil or Asc-usmentioning
confidence: 99%